IMPROVING THE ECONOMIC MECHANISMS OF STATE REGULATION OF THE REAL SECTOR - Abdulhamidov , Abdullajon (Scientific practical conference, 2026)
The article below provides information about the current state intervention in the economy to a certain extent and the privatization of state property. It is worth mentioning that in our country the esteemed President Shavkat Miromonovich Mirzeyoyev created ample opportunities for the development of entrepreneurship and privatization of state property.